2017
DOI: 10.3389/fimmu.2017.00449
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and Molecular Heterogeneity of RTEL1 Deficiency

Abstract: Typical features of dyskeratosis congenita (DC) resulting from excessive telomere shortening include bone marrow failure (BMF), mucosal fragility, and pulmonary or liver fibrosis. In more severe cases, immune deficiency and recurring infections can add to disease severity. RTEL1 deficiency has recently been described as a major genetic etiology, but the molecular basis and clinical consequences of RTEL1-associated DC are incompletely characterized. We report our observations in a cohort of six patients: five w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 54 publications
3
58
0
Order By: Relevance
“…RTEL1 encodes the regulator of telomere elongation helicase 1, which is essential for telomere maintenance and regulation of homologous recombination. Germline biallelic RTEL1 variants are responsible for dyskeratosis congenita and its severe variant Hoyeraal-Hreidarsson syndrome, 39 while heterozygous carriers with pulmonary fibrosis, [40][41][42] myelodysplasia and liver disease have been described. 43 Thus, our findings on FANCI, MAST1, POLH and RTEL1 would warrant further investigation in other large-scale studies on familial BC and the setup of functional studies to assess the impact of the variants.…”
Section: Discussionmentioning
confidence: 99%
“…RTEL1 encodes the regulator of telomere elongation helicase 1, which is essential for telomere maintenance and regulation of homologous recombination. Germline biallelic RTEL1 variants are responsible for dyskeratosis congenita and its severe variant Hoyeraal-Hreidarsson syndrome, 39 while heterozygous carriers with pulmonary fibrosis, [40][41][42] myelodysplasia and liver disease have been described. 43 Thus, our findings on FANCI, MAST1, POLH and RTEL1 would warrant further investigation in other large-scale studies on familial BC and the setup of functional studies to assess the impact of the variants.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, TINF2-mutated patients generally display poor outcome due to the severity of the disease, regardless of cancer [124]. RTEL1 mutations account for 5% of DC cases and are associated with heterogeneous clinical manifestations ranging from mild hypocellular bone marrow with B/NK cell lymphopenia to early, very severe cellular deficiency [57]. In addition, other pathological manifestations may be displayed by patients carrying nonsense mutations in RTEL1 gene such as early onset of thrombocytopenia, anemia, microcephaly, developmental delay, and cerebellar hypoplasia [62].…”
Section: Dyskeratosis Congenitamentioning
confidence: 99%
“…The patients reported by STUART et al [15] were considered to be extensively reported by NEWTON et al [7]. Five articles with clinical data and the present cohort were finally conserved for analysis [7,10,14,17].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…RTEL1 is a DNA helicase playing roles in DNA replication, genome stability, DNA repair and telomere maintenance [8]. Bi-allelic mutations in RTEL1 have been reported in patients with Hoyeraal-Hreidarsson syndrome (see the Online Mendelian Inheritance in Man (OMIM) Catalogue; entry #305000, www.omim.org/), a severe variant of short telomere syndrome characterised by early-onset bone marrow failure, immunodeficiency and developmental defects associated with abnormally short telomeres, as well as myelodysplasia and liver disease [9][10][11][12][13][14]. Heterozygous RTEL1 mutations are also detected in 5-9% of patients with familial forms of ILD [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%